1995
DOI: 10.1063/1.359083
|View full text |Cite
|
Sign up to set email alerts
|

Polarization suppression in Pb(Zr,Ti)O3 thin films

Abstract: Switchable polarization can be suppressed in Pb(Zr,Ti)O3 thin films by optical, thermal, electrical, and reducing processes. The optical suppression effect occurs by biasing the ferroelectric near the switching threshold and illuminating the material with band gap light; the thermal suppression effect occurs by biasing the ferroelectric near the switching threshold and heating the material to ≊100 °C. The electrically induced suppression effect, known as electrical fatigue, occurs by subjecting the ferroelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
102
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(113 citation statements)
references
References 23 publications
11
102
0
Order By: Relevance
“…It could be surmised that the presence of ionic defects ͑e.g., oxygen vacancies͒ or electronic charge carriers could possibly lead to elongated lattice parameters 54 or would pin domain walls 55,56 and therefore reduce the measured switchable polarization. While we cannot fully neglect the effect of oxygen vacancies, generally such ionic vacancies are expected to increase leakage currents dramatically.…”
Section: -7mentioning
confidence: 99%
“…It could be surmised that the presence of ionic defects ͑e.g., oxygen vacancies͒ or electronic charge carriers could possibly lead to elongated lattice parameters 54 or would pin domain walls 55,56 and therefore reduce the measured switchable polarization. While we cannot fully neglect the effect of oxygen vacancies, generally such ionic vacancies are expected to increase leakage currents dramatically.…”
Section: -7mentioning
confidence: 99%
“…On the other hand, the term ageing normally refers to a timedependent decay of the dielectric and piezoelectric properties in the absence of any external stimulus. 4 Several different mechanisms have been identified as the origin of fatigue in ferroelectrics; these include microcrack growth and coalescence due to internal residual stresses, 5,6 space charge formation, 2 and point defect clustering. [7][8][9] The development of fatigue depends on a variety of factors such as the nature of the load (electrical, mechanical), 9,10 type of waveform (unipolar, bipolar, sesquipolar), 11,12 frequency, 13 the chemical composition and structure/microstructure of the material, 14 and other environmental factors such as temperature.…”
mentioning
confidence: 99%
“…[1][2][3] In this context, the term fatigue is usually employed to describe changes in the functional properties over time as a result of static or alternating electrical and mechanical loads. On the other hand, the term ageing normally refers to a timedependent decay of the dielectric and piezoelectric properties in the absence of any external stimulus.…”
mentioning
confidence: 99%
“…5,6 Previous studies have shown that planar ordering of oxygen vacancies occurs in perovskites with an increase in defect density, [7][8][9][10][11] with a minority of vacancies remaining as uncorrelated point defects. Reflection highenergy electron diffraction studies by Matsumoto et al 12 of SrTiO 3 have shown that oxygen vacancies form a superstructure on a nanometer scale, further confirming the hypothesis that oxygen vacancies in pervoskites form an ordered network. With an increase in concentration, oxygen vacancies cluster, initially in one-dimensional ͑1D͒ chains and above a certain density in planes of specific geometries.…”
mentioning
confidence: 48%